2013
DOI: 10.1002/2013gc005031
|View full text |Cite
|
Sign up to set email alerts
|

Imaging slow slip fronts in Cascadia with high precision cross‐station tremor locations

Abstract: [1] We apply a new method to obtain accurate locations of tremor sources beneath southern Vancouver Island. Unlike more standard ''cross-time'' methods, which compare waveforms from different time windows at the same station, this ''cross-station'' method compares waveforms from the same time window at widely separated stations. It performs well, relative to cross-time methods, when the response to an impulsive tremor source is dominated by the main arrival rather than coda and when multiple colocated sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
140
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(170 citation statements)
references
References 53 publications
(119 reference statements)
25
140
3
Order By: Relevance
“…At the time the lack of precise tremor hypocenters fuelled the debate regarding the nature of the tremor signal, whether it was occurring within the overriding plate as the slow slip was progressing and changing the stress field to generate hydraulic fracturing (Kao et al, 2005;Rogers and Dragert, 2003), or via direct shear slip on the plate interface during slow slip (Shelly et al, 2006(Shelly et al, , 2007. Low Frequency earthquakes (LFE) families that form at least part of the tremor during slow slip have now been found all along the Cascadia margin (Plourde et al, 2015;Royer and Bostock, 2014;Thomas and Bostock, 2015) and are consistent with shear slip on the plate interface (see also Rubin and Armbruster, 2013;Armbruster et al, 2014, for tremor locations). Interestingly, the location of LFE epicenters and inferred slow slip regions appears to coincide with the low-velocity signature inferred to be the downgoing oceanic crust (e.g., Audet (Christensen, 1984(Christensen, , 1996.…”
Section: Accepted M Manuscriptmentioning
confidence: 90%
“…At the time the lack of precise tremor hypocenters fuelled the debate regarding the nature of the tremor signal, whether it was occurring within the overriding plate as the slow slip was progressing and changing the stress field to generate hydraulic fracturing (Kao et al, 2005;Rogers and Dragert, 2003), or via direct shear slip on the plate interface during slow slip (Shelly et al, 2006(Shelly et al, , 2007. Low Frequency earthquakes (LFE) families that form at least part of the tremor during slow slip have now been found all along the Cascadia margin (Plourde et al, 2015;Royer and Bostock, 2014;Thomas and Bostock, 2015) and are consistent with shear slip on the plate interface (see also Rubin and Armbruster, 2013;Armbruster et al, 2014, for tremor locations). Interestingly, the location of LFE epicenters and inferred slow slip regions appears to coincide with the low-velocity signature inferred to be the downgoing oceanic crust (e.g., Audet (Christensen, 1984(Christensen, , 1996.…”
Section: Accepted M Manuscriptmentioning
confidence: 90%
“…Previously proposed mechanisms such as large-scale fluid flow 6 may be physically implausible, whereas fast migration as simply an apparent velocity of much slower propagation 9 does not seem to explain the patterns of tremor propagation along both strike and dip in Cascadia 17 . Higher propagation velocities kinematically imply higher average slip speeds and/or smaller stress drops 11,17 , but the physics underlying this difference remains largely unknown.…”
Section: High-speed Tremor Migration and Its Regulating Mechanismmentioning
confidence: 99%
“…This high-speed migration seems to occur in the orientation of relative plate motion 6 , which is roughly the dip direction for subduction zones but along strike for the San Andreas. Recently, tremor propagation with intermediate velocities (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) km h −1 ) has also been observed, termed 'rapid tremor reversal' events because they propagate primarily backwards from the direction of overall slow slip propagation 8 . Multiple mechanisms have been put forth to explain the varied migration behaviours, such as large-scale fluid flow 6 , interaction of slow propagation with slip-aligned heterogeneity 9,10 , or a two-state-variable friction law 11 .…”
mentioning
confidence: 99%
“…Gibbons & Ringdal (2009) found that while extended source time functions lead to complicated cross-correlations, the same complications are often observed across a range of stations. Some researchers even use such complex but consistent source time functions to identify tremor without a template event: by searching for waveforms that are similar at multiple stations (Rubin & Armbruster 2013;Armbruster et al 2014;Peng et al 2015;Savard & Bostock 2015). However, for the waveforms to be similar, the stations used must have similar Green's functions.…”
Section: Introductionmentioning
confidence: 99%
“…Only the relative phases of the source time functions will remain. These relative source time function phases may be complicated, but we expect them to be the same among the observing stations, as seen in cross-station tremor processing (Rubin & Armbruster 2013;Armbruster et al 2014;Peng et al 2015;Savard & Bostock 2015). We can therefore determine if the two sources are co-located by examining whether the cross-correlation phases are coherent across stations.…”
Section: Introductionmentioning
confidence: 99%